Activities of Teenagers involved in the Pinamou Tradition in Central Maluku - Nastain (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
This research aims to reveal the activities of teenagers involved in the Pinamou tradition of the Nuaulu Tribe in Central Maluku. The type of research is qualitative with an ethnographic approach. The informants in this study were three teenage girls, two teenage parents, one traditional leader, and one community leader. Data collection methods through in-depth interviews and observation. Data analysis uses domain analysis. The research results revealed that the Pinamou Tradition is intended for young women of the Nuaulu tribe and is carried out during their first menstruation, which indicates that the young women have entered adulthood. Activities that teenagers are not allowed to do in this tradition include not being seen by adult men, not being able to bathe, and not speaking loudly. The recommended thing is to use charcoal to cover the face as protection from supernatural beings. The provisions in the Pinamou tradition carried out by teenagers are believed to protect them from danger despite many restrictions on activities.